2017
DOI: 10.4103/jnrp.jnrp_11_17
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Involvement in Patients with Guillain–Barré Syndrome in Subacute Phase

Abstract: Objectives:To evaluate the pulmonary function in Guillain–Barre syndrome (GBS) patients in subacute phase and find clinical correlates of pulmonary dysfunction.Methods:This was a single-center, prospective, cross-sectional, hospital-based study in GBS patients performed in Department of Neurological Rehabilitation at a tertiary care institute. Clinical examination for pulmonary function was done by measuring chest expansion. The pulmonary function tests were carried out by Spirometry kit Microquark Cosmed, Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In Guillain-Barré syndrome (GBS), an acute inflammatory polyradiculoneuropathy, presenting sensorimotor symptoms predominate and can be severe, causing respiratory weakness that may progress rapidly to become life threatening. Restrictive lung disease is found in 79% of GBS patients in the subacute phase [139], and 20-30% of GBS patients require mechanical ventilation [140].…”
Section: Guillain-barré Syndrome (Gbs Also Known As Acute Inflammator...mentioning
confidence: 99%
“…In Guillain-Barré syndrome (GBS), an acute inflammatory polyradiculoneuropathy, presenting sensorimotor symptoms predominate and can be severe, causing respiratory weakness that may progress rapidly to become life threatening. Restrictive lung disease is found in 79% of GBS patients in the subacute phase [139], and 20-30% of GBS patients require mechanical ventilation [140].…”
Section: Guillain-barré Syndrome (Gbs Also Known As Acute Inflammator...mentioning
confidence: 99%
“…Conflicting reports have suggested that not all GBS patients have favourable responses to exercise [45,46]. A lack of improvement in residual fatigue may not be easy to rationalise, due to the absence of an underlying pathophysiological mechanism (such as nerve dysfunction, anaemia, hypothyroidism, diabetes, or chronic illness) [7,30]. However, it is important to consider whether persistent fatigue may be due to a psychiatric mechanism (e.g., depression) that hampers recovery independent of exercise-induced improvements in muscle strength [28].…”
Section: A Multidisciplinary Team Approach For the Management Of Gbsmentioning
confidence: 99%
“…The natural history of the disease involves an acute phase characterised by physical disability which reaches a plateau within two weeks. Timely clinical management is required due to the risk for respiratory failure resulting from dysfunction of the phrenic nerve, with 20%-30% of patients requiring assisted ventilation [1,6,7]. Early signs of respiratory failure include tachypnoea, tachycardia and air hunger, while late signs include use of accessory respiratory muscles, paradoxical breathing and orthopnoea due to diaphragmatic paresis [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study published in the current issue titled, “Pulmonary involvement in patients with Guillain- Barré syndrome in sub-acute phase”[ 9 ] highlights the impairment in lung function after acute illness and attempts correlation with clinical parameters at presentation and outcome measures in subacute phase. Chest expansion has been found to be an easily measurable variable which is statistically related to pulmonary dysfunction.…”
mentioning
confidence: 99%